2009
DOI: 10.1111/j.1747-4949.2009.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Case Fatality of Subarachnoid Haemorrhage in Northern Greece: The Evros Registry of Subarachnoid Haemorrhage

Abstract: The incidence and case-fatality rate of subarachnoid haemorrhage haemorrhage in Greece appear to be similar to other developed countries. No gender differences in subarachnoid haemorrhage incidence and case-fatality rate were documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…4 These data are consistent with studies that show that the incidence of aSAH increases with age, with a typical average age of onset in adults Ն50 years of age. 3,7,17,18 aSAH is relatively uncommon in children; incidence rates increase as children get older, with incidence ranging from 0.18 to 2.0 per 100 000. 4, 19 The majority of studies also indicate a higher incidence of aSAH in women than in men.…”
Section: Incidence and Prevalence Of Asahmentioning
confidence: 99%
See 1 more Smart Citation
“…4 These data are consistent with studies that show that the incidence of aSAH increases with age, with a typical average age of onset in adults Ն50 years of age. 3,7,17,18 aSAH is relatively uncommon in children; incidence rates increase as children get older, with incidence ranging from 0.18 to 2.0 per 100 000. 4, 19 The majority of studies also indicate a higher incidence of aSAH in women than in men.…”
Section: Incidence and Prevalence Of Asahmentioning
confidence: 99%
“…60 Others have shown that case fatality rates decreased from 57% in the mid-1970s to 42% in the mid-1980s, 11 whereas rates from the mid-1980s to 2002 are reported to be anywhere from 26% to 36%. 6,12,13,18,20,61,62 Mortality rates vary widely across published epidemiological studies, ranging from 8% to 67%. 59 Regional variations become apparent when numbers from different studies are compared.…”
Section: Natural History and Outcome Of Asahmentioning
confidence: 99%
“…Nevertheless, research on stroke incidence, case fatality and distribution of stroke types in Greece is scarce. In this context, previous salient epidemiological data on stroke incidence stem from two prospective, population-based registers: one investigating ischemic and hemorrhagic stroke types, conducted over a decade ago [3] and more recently another study focusing on subarachnoid haemorrhage [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Because death resulting from SAH often occurs before hospital admission (10-20 % of cases) [3,4] the true incidence of SAH could be even higher. Although a number of population based studies have indicated that the incidence of SAH remained relatively stable over the last four decades [2,5,6], a recent review, with data adjusted for age and sex, suggested a slight decrease in incidence between 1950 and 2005 for regions except Japan, South and Central America and Finland [1,7,8]. These data are consistent with studies that show that the incidence of SAH increases with age, with a typical average age of onset in adults C50-years-old [1,7,8].…”
Section: Epidemiology Of Sahmentioning
confidence: 97%